Cardiomyopathy in patients with liver cirrhosis: review article - González-Domínguez, Esteban; Córdova, Diego; Abad, Paula; González, Eduardo; González, Camila; José Cordero, Juan (Hepatología, 2022)
Cirrhotic cardiomyopathy is a complication in cirrhotic patients, with a prevalence of more than 40%. During the resting state, it is a subclinical entity, which triggers symptoms upon exercise or circulatorystress. Its pathophysiology is explained by portal hypertension leading to splanchnic vasodilatation, with subsequent release of vasodilators and cardio-suppressive factors, which leads to hyperdynamic circulation and circulatory dysfunction, with elevated cardiac output, decreased vascular resistance and low blood pressure. The main characteristics are systolic and diastolic cardiac dysfunction, hyperdynamic circulation and electrophysiological alterations, especially prolongation of the QT interval. Echocardiography and physical or pharmacological stress tests are used in diagnosis. There is not an standardized treatment protocol. Liver transplantation can be an effective procedure to reverse cardiac dysfunction in selected patients. In this review, we describe the characteristics of cirrhotic cardiomyopathy and its role in the morbidity and mortality of the patient with cirrhosis.